PENEGAKAN HUKUM YANG BERKEADILAN DALAM PERSPEKTIF FILSAFAT HERMENEUTIKA HUKUM (Suatu Solusi Terhadap Problematika Penegakan Hukum Di Indonesia) - Agus Budi Susilo (Jurnal Hukum dan Peradilan, 2013)
The essence of the rule of law is justice. Justice has many meanings, depending on the perspective. Every country often arise various problems, related to the administration of justice in the realm of law. The concept of justice that have been established in a country is not necessarily better when applied to other countries. However, it is possible to mutual influenced or be integrated between each other thinking about the meaning of justice, particularly those having a universal nature. At the philosophical level, each country has own thoughts of the roots, depending on the basic norms and socio-cultural life of the nation. Thus, about the meaning of justice from the view of philosophy, the proper tools are used is hermeneutic. Search justice in the perspective of hermeneutics in the context of law enforcement should also be framed by the perspective of jurisprudence, in order to obtain the intersection and its implementation easier. Keywords: Justice, Hermeneutics, Legal Studies and Law Enforcement.